L’empatia come rispecchiamento creativo. Merleau-Ponty e la tesi della reversibilità - Pasquinucci, Pietro (Bollettino Filosofico, 2022)
Beginning with the analysis of the phenomenological approach to the question of empathy, this essay dwells upon some contemporary interpretations of Merleau-Ponty’s reflection on intersubjectivity. These interpretations claim that, according to Merleau-Ponty, the empathic experience is made possible by a category that belongs to the self. This category would be prior to any concrete encounter with other subjects. Contrasting with these positions, this essay outlines that, according to Merleau-Ponty, the empathic experience is not preceded by an internal category; rather, it is made possible by a particular structure of the perceptual experience, i.e., by its expressiveness. Drawing on these considerations, the final part of the paper underlines the meaning of the empathic experience as engendered by this fundamental expressivity of perception. Keywords: Empathy, Expression, Merleau-Ponty, Phenomenology, Reversibility